2020
DOI: 10.3390/rs12060915
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Workflow Feature Selection on Forest LAI Prediction with Sentinel-2A MSI, Landsat 7 ETM+ and Landsat 8 OLI

Abstract: The European Space Agency (ESA)’s Sentinel-2A (S2A) mission is providing time series that allow the characterisation of dynamic vegetation, especially when combined with the National Aeronautics and Space Administration (NASA)/United States Geological Survey (USGS) Landsat 7 (L7) and Landsat 8 (L8) missions. Hybrid retrieval workflows combining non-parametric Machine Learning Regression Algorithms (MLRAs) and vegetation Radiative Transfer Models (RTMs) were proposed as fast and accurate methods to infer biophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 76 publications
1
31
0
Order By: Relevance
“…The results of our sensitivity analysis provided clear insights into which biophysical variables can be measured using S2 data (see Figure 5 and Table 3), and furthermore, provided insights into the effects of their interaction with spectral responses. Our results on the band correlation (Table 3) and sensitivity analysis ( Figure 5) are in line with previous results [52], and in particular, when compared with recent results by Brede et al [27] also on S2 data, and Gu et al [49] on Landsat TM data. Similarly, both studies found that C ab was associated with the visible range in Landsat TM bands, and that C m , C w and LAI was associated with NIR and SWIR bands (see Figure 5).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The results of our sensitivity analysis provided clear insights into which biophysical variables can be measured using S2 data (see Figure 5 and Table 3), and furthermore, provided insights into the effects of their interaction with spectral responses. Our results on the band correlation (Table 3) and sensitivity analysis ( Figure 5) are in line with previous results [52], and in particular, when compared with recent results by Brede et al [27] also on S2 data, and Gu et al [49] on Landsat TM data. Similarly, both studies found that C ab was associated with the visible range in Landsat TM bands, and that C m , C w and LAI was associated with NIR and SWIR bands (see Figure 5).…”
Section: Discussionsupporting
confidence: 93%
“…Model performance was severely affected even at low levels of noise (Figures 8 and 9). This is of particular concern given that every data has noise, and previous research has shown that the Sen2Cor atmospheric correction algorithm produces between 5% and 10% noise [27,52]. Moreover, and in contrast to results obtained on pure data, both neural networks generally performed better than GPR when noise was added, which indicates that further developments with GPR are needed to be able to deal effectively with noisy observations.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations